Beyond Traditional Boundaries: Hennyhenna Art’s Marketing Innovation - Samri Juliati Nasution, Yenni; Setiani, Henni; Uljannah, Annisa (Taqaddum: Community Service Journal, 2023)
This study aims to understand how Hennyhenna Art, a small business in the field of henna art, is able to transcend traditional boundaries through marketing innovation in the digital era to achieve competitive advantage. The research methods used situational approach allow researchers to understand the specific physical context of Hennyhenna Art's marketing innovations in the digital era, including factors that affect marketing strategies and competitive advantages in certain situations. The results show that Hennyhenna Art has successfully utilized various digital platforms and social media to market its products and services, reach a wider audience, and build closer relationships with its customers. In addition, Hennyhenna Art continues to innovate in creating unique and attractive henna designs, as well as adjusting its services to the trends and needs of consumers in the digital era. This strategy has helped Hennyhenna Art achieve competitive advantage in a highly competitive market.